Analysis of Studies on the Role of Hormones in Micropenis Disorders: A Systematic Literature Review - Amal, Rizki Jaya; Irfansyah; Muhammad Arif Hasan; Aulia Putra Rahman (HM Publisher, 2023)
A deep understanding of the role of specific hormones in genital development is key to designing effective therapeutic approaches. Factors such as testosterone deficiency, growth hormone disorders, or other hormonal imbalances can be targets for hormonal interventions that can affect penis size. This study aimed to explore the role of hormonal aspects in micropenis disorders. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the role of hormonal aspects in micropenis disorders. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Aspects of the hormonal role in micropenis include several key elements that influence the development of genital organs in men. Hormones, such as testosterone, growth hormone, estrogen, and dihydrotestosterone (DHT), play an important role in stimulating penis growth and development. Proper hormonal balance is necessary for normal genital development, and disturbances in the production of or response to these hormones may contribute to conditions such as micropenis.